Effects and Potential Mechanisms of Pioglitazone on Lipid Metabolism in Obese Diabetic KKAy Mice - Jun Peng; Yi Huan; Qian Jiang; Su-juan Sun; Chun-ming Jia; Zhu-fang Shen (PPAR Research)
This study aimed to analyze the effects and potential mechanisms of pioglitazone on triglyceride and cholesterol metabolism in obese diabetic KKAy mice. Pioglitazone was orally administered to KKAy mice over 30 days. Compared to C57BL/6J mice, KKAy mice developed obvious insulin resistance, hepatic steatosis, and hyperlipidemia. Pioglitazone treatment resulted in deteriorated microvesicular steatosis and elevated hepatic triglyceride levels, though plasma triglyceride and free fatty acid levels were reduced by the treatment, compared to nontreated KKAy mice. Plasma alanine aminotransferase activities were also significantly increased. Additionally, pioglitazone increased plasma concentrations of total cholesterol, HDL-cholesterol, and LDL-cholesterol but decreased hepatic cholesterol. Gene expression profiling revealed that pioglitazone stimulated hepatic peroxisome proliferator-activated receptor gamma hyperactivity, and induced the upregulation of adipocyte-specific and lipogenesis-related genes but downregulated of genes involved in triglyceride lipolysis and fatty acid β-oxidation. Pioglitazone also regulated the genes expression of hepatic cholesterol uptake and excretion, such as low density lipoprotein receptor (LDL-R) and scavenger receptor type-BI (SR-BI). These results suggested that pioglitazone could induce excessive hepatic triglyceride accumulation, thus aggravating liver steatosis and lesions in KKAy mice. Furthermore, pioglitazone may suppress the clearance of serum cholesterol from the liver predominantly through inhibition of LDL-R and SR-BI expression, thus increasing the plasma cholesterol.